Integrating DSM/ICD, Research Domain Criteria, and Descriptive Psychopathology in Teaching and Practice of Psychiatry - Fluyau, Dimy (Frontiers in Psychiatry, 2018)
Background: Some believe that Psychiatry relies solely on the Diagnostic and Statistical Manual of Mental Disorders (DSM). Some are not aware of the effort initiated by the Research Domain Criteria (RDoC) to propel the field to a new era of Medicine. Others are not acquainted with studies of Descriptive Psychopathology that can dissect symptoms and signs of mental illness and convert them into reliable clinical data for diagnosis and treatment purpose. This document is to bring keenness of the advances in research, translational or clinical, made in Psychiatry, and to encourage students, psychiatric residents, as well as psychiatric practitioners to integrate DSM/ICD, RDoC, and Descriptive Psychopathology into teaching and practice. Methods: A search of the literature originated from 1985 to 2018 on two central databases: Google Scholar and Pubmed by free-texting: “comparison, strengths and weaknesses, Diagnostic and Statistical Manual of Mental Disorders, Research Domain Criteria, and Descriptive Psychopathology.” Results: The DSM and ICD possess algorithms for psychiatric diagnosis, but they are limited to determine psychobiological causes of mental illnesses. Descriptive Psychopathology aims to dissect the mind to understand better “signs and symptoms,” their psychological, neurological, or neuropsychological origins but has been criticized for being non-reliable to practically explain the meaning of signs and symptoms that it attempts to describe. The RDoC claims to be a data-driven system of biological and psychological research for an evidence-based approach to Psychiatry. It is said that RDoC utilizes translational research that has been very slow to move to human experimentation. Discussion and conclusion: Despite incommensurable translational research and human trials, the integration of translational research (neurosciences, experimental psychology, and genomics) as available human research data into teaching and practice is lacking. The author believes that the integration will enhance scientific and well-founded communication with our peers, advance psychopharmacologic treatments and improve our patient's mental well-being.